2012
DOI: 10.1124/jpet.112.193425
|View full text |Cite
|
Sign up to set email alerts
|

Adenylyl Cyclase 2 Selectively Couples to E Prostanoid Type 2 Receptors, Whereas Adenylyl Cyclase 3 Is Not Receptor-Regulated in Airway Smooth Muscle

Abstract: Adenylyl cyclases (ACs) are important regulators of airway smooth muscle function, because ␤-adrenergic receptor (␤AR) agonists stimulate AC activity and cAMP production. We have previously shown in a number of cell types that AC6 selectively couples to ␤AR and these proteins are coexpressed in lipid rafts. We overexpressed AC2, AC3, and AC6 in mouse bronchial smooth muscle cells (mBSMCs) and human embryonic kidney (HEK)-293 cells by using recombinant adenoviruses and assessed their localization and regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 47 publications
4
34
0
1
Order By: Relevance
“…AC2 is also stimulated in a PKC-independent manner by Ga s in response to activation of G s -coupled receptors and directly via the small molecule AC activator forskolin. PGE 2 is known to bind and activate the G s -coupled EP2/4 prostanoid receptors that are endogenously expressed in HEK293 cells (Willoughby et al, 2007;Bogard et al, 2012). As expected, PGE 2 treatment resulted in a concentration-dependent increase in cAMP accumulation in HEK-hAC2 cells (EC 50 : 160 6 78 nM, n 5 3).…”
Section: Resultsmentioning
confidence: 67%
“…AC2 is also stimulated in a PKC-independent manner by Ga s in response to activation of G s -coupled receptors and directly via the small molecule AC activator forskolin. PGE 2 is known to bind and activate the G s -coupled EP2/4 prostanoid receptors that are endogenously expressed in HEK293 cells (Willoughby et al, 2007;Bogard et al, 2012). As expected, PGE 2 treatment resulted in a concentration-dependent increase in cAMP accumulation in HEK-hAC2 cells (EC 50 : 160 6 78 nM, n 5 3).…”
Section: Resultsmentioning
confidence: 67%
“…Toll-like receptor 4 is associated with AC6 in lipid rafts in a murine macrophage cell line (24), while stomatin-related olfactory protein and AC3 are found in lipid rafts in olfactory cilia (22). By contrast, AC2 and E prostanoid type 2 receptors are found in non-lipid rafts in mouse bronchial smooth muscle cells (21). …”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that several GPCRs use a specific AC isoform for cAMP production. For example, in mouse smooth muscle cells and HEK-293 cells, AC2 and AC6 mediate cAMP increase induced by EP2 and ADRB2, respectively (Bogard et al, 2012). Consistent with specific GPCR-AC coupling as such, subcellular fractionation showed that ADRB2 and AC6 are localized in lipid rafts, from which EP2, AC2, and AC7 are excluded (Crossthwaite et al, 2005;Bogard et al, 2012).…”
Section: Discussionmentioning
confidence: 84%
“…For example, in mouse smooth muscle cells and HEK-293 cells, AC2 and AC6 mediate cAMP increase induced by EP2 and ADRB2, respectively (Bogard et al, 2012). Consistent with specific GPCR-AC coupling as such, subcellular fractionation showed that ADRB2 and AC6 are localized in lipid rafts, from which EP2, AC2, and AC7 are excluded (Crossthwaite et al, 2005;Bogard et al, 2012). Likewise, D1 receptors that are coupled to AC6 without EP1 and those that are coupled to AC7 with EP1 could be localized in different membrane domains, lipid raft domains, and nonlipid raft domains, respectively.…”
Section: Discussionmentioning
confidence: 99%